A reference high-pressure CO2 adsorption isotherm for ammonium ZSM-5 zeolite: results of an interlaboratory study - Nguyen, H. G. T.; Espinal, Laura; Van Zee, R. D.; Thommes, M.; Toman, B.; Hudson, M. S. L.; Mangano, Enzo; Brandani, S.; Broom, D. P.; Benham, M. J.; Cychosz, K.; Bertier, Pieter G.C.; et al. (Adsorption-Journal of the International Adsorption Society, 2018)
This paper reports the results of an international interlaboratory study led by the National Institute of Standards and Technology (NIST) on the measurement of high-pressure surface excess carbon dioxide adsorption isotherms on NIST Reference Material RM 8852 (ammonium ZSM-5 zeolite), at 293.15 K (20 °C) from 1 kPa up to 4.5 MPa. Eleven laboratories participated in this exercise and, for the first time, high-pressure adsorption reference data are reported using a reference material. An empirical reference equation nex=d(1+exp[(-ln(P)+a)/b])c, [nex-surface excess uptake (mmol/g), P-equilibrium pressure (MPa), a = −6.22, b = 1.97, c = 4.73, and d = 3.87] along with the 95% uncertainty interval (Uk = 2 = 0.075 mmol/g) were determined for the reference isotherm using a Bayesian, Markov Chain Monte Carlo method. Together, this zeolitic reference material and the associated adsorption data provide a means for laboratories to test and validate high-pressure adsorption equipment and measurements. Recommendations are provided for measuring reliable high-pressure adsorption isotherms using this material, including activation procedures, data processing methods to determine surface excess uptake, and the appropriate equation of state to be used.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Carbon dioxide; High-pressure adsorption isotherm; Interlaboratory study; Reference adsorbent material; Reference isotherm; RM 8852; Surface excess adsorption; ZSM-5